The analysis of languages in contact: A case study through a variationist lens - Ana Maria Carvalho (Cadernos de Estudos Lingüísticos, 2016)
This article discusses the contributions made by variationist sociolinguistics to the study of languages in contact. After summarizing the development of this subfield and its theoretical and methodological implications, 3rd p.sg. subject pronoun expression is examined in Portuguese and Spanish in contact in Northern Uruguay. Based on comparative sociolinguistics, the results show that this variable use among bilinguals does not converge into a single system. Lastly, it calls for more studies in Portuguese dialects in contact with other languages that follow the framework of variationist sociolinguistics.